Study of emotional state effect on decision making by using fNIRS - Chong, J.S. (Institute of Electrical and Electronics Engineers Inc., 2019)
The paper studies the effect of emotional states modulated by auditory stimuli on the cognitive control on decision making. Based on other previous neuroimaging studies, functional near-infrared spectroscopy provided reliable neuroimaging measurement in analyzing emotional states by studying the changes of hemodynamic response in prefrontal cortex (PFC). This experiment involved 16 nursing students. During the experiment, participants were given one minute to complete five nursing practice questions with five sequential repetitions in the presence of neutral and negative emotional auditory stimuli in two separated sessions under fNIRS measurement. The sound stimuli was selected from the International Affective Digitized Sound (IADS) System. The neutral auditory stimuli had neutral valence and medium arousal rating whereas negative auditory stimuli had negative valence and high arousal rating. The data collected was preprocessed by using wavelet transform to decompose the data into different frequency intervals. By selecting the frequency interval of interest, we analyzed the data based on functional connectivity within prefrontal cortex regions. We computed the regional wavelet coherence values between affective and neutral tasks. From the behavioral analysis, we found that subjects had significantly higher accuracy in affective task compared to neutral task. Based on the analysis, we found that left prefrontal cortex produced significantly lower wavelet coherence value but the highest coherence-accuracy correlation in affective task than in neutral task. Â© 2019 IEEE.